THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND SERVICE QUALITY ON THE EFFECTIVENESS OF LAND SERVICE DIGITALIZATION - Ach Backhrurozak; Agus Widodo; Moh. Khusaini (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2026)
The purpose of this study is to examine how transformational leadership and service quality affect how well land service digitization is implemented in public sector companies. Digital transformation in land services not only requires technological readiness, but also requires adequate leadership support and service quality to ensure the successful implementation of electronic systems. This study uses a quantitative approach with an explanatory design and is analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Data was collected through a questionnaire of 75 employees who were directly involved in the implementation of digital services at the Sidoarjo Regency Land Office. The results of the analysis showed that transformational leadership had a positive and significant effect on the effectiveness of digitalization implementation with a coefficient of 0.558 and a significance value below 0.05. Service quality also has a positive and significant effect with a coefficient of 0.718, and has a more dominant influence than transformational leadership. The research model has a strong explainability with an R-square value of 0.744. These findings show that the success of land service digitization is more determined by the quality of the system and digital services that users feel, along with transformative leadership support. This research implies that increasing the effectiveness of digitalization requires strengthening leadership and improving service quality simultaneously.